Prevalence, predisposing factors, and turnover intention related to low back pain among health workers in Accra, Ghana. - Philip Apraku Tawiah; Emmanuel Appiah-Brempong; Paul Okyere; Geoffrey Adu-Fosu; Mary Eyram Ashinyo (PLoS ONE)
Background Globally, low back pain (LBP) is responsible for disability among 60.1 million people. Health workers face a higher likelihood of being exposed to LBP compared to employees in the construction and manufacturing sectors. Data on LBP among hospital workers in Ghana are however limited. This study examined the prevalence, predisposing factors and turnover intention related to LBP among health workers in the Greater Accra region of Ghana. Methods A multi-centred facility-based cross-sectional study was conducted in the Greater Accra region from January 30 -May 31, 2023. A multi-stage sampling technique was adopted, and the study participants were selected through proportion-to-size simple random sampling. STATA 15 software was used for analysis. Logistic regression analysis was used to determine the factors associated with LBP at a p < 0.05. Results A survey was conducted among 607 health workers in 10 public and private hospitals. The prevalence of LBP was 81.6% [95% CI: (78.2%-84.6%)]. Advanced age [AOR = 1.07 (1.00, 1.16)], working for more than 5 days in a week [AOR = 8.14 (2.65, 25.02)], working overtime [AOR = 2.00 (1.16, 3.46)], rarely involved in transferring patients [AOR = 3.22 (1.08, 9.60)], most of the time involved in transferring patients [AOR = 6.95 (2.07, 23.26)], awkward posture during work [(AOR = 2.36 (1.31, 4.25)], perceived understaffing [(AOR = 1.84 (95% CI = 1.04-3.27)], sleep duration ≥ 8 [AOR = 0.54 (0.31, 0.97)] and sitting intermittently at work [AOR = 0.31 (0.12, 0.80)] were factors significantly associated with LBP. A substantial number, 123 (24.9%), occasionally had intention of leaving their jobs. Conclusion The study revealed a high proportion of low back pain (LBP), and turnover intention attributed to LBP. Moreover, organizational and occupational factors were found to be significantly associated with LBP. These findings underscore the importance of targeted interventions aimed at reducing the burden of LBP within these specific areas.